GENDER WRITING STYLES OF BATAKNESE AND JAVANESE SENIOR HIGH SCHOOL STUDENTS IN WRITING ARGUMENTS - Sri Rebeka J. A. Parhusip; Berlin Sibarani (Universitas Negeri Medan, 2021)
The objectives of this study are to describe the characteristics of gender writing style ofBataknese and Javanese students and to describe the reason ofmale and female Bataknese andJavanese students’ writing style characteristics the way they do. This resesarch wasconducted at SMAN 1 Onanrunggu and SMAN 2 Percut Sei Tuan. The mwthod of thisresearch was qualitative desctiptive research. The subjects of this research were XI gradestudents of SMAN Onanrunggu and SMAN 2 Percut Sei Tuan. The technique ofdatacollection was writing assignment. The research finding showed that in writingargumentative text, the writing style characteristics of each gender of Bataknese and Javanesestudents were different. The writing style characteristics of Male Bataknese Senior HighSchool studentsare strong, convincing, logical and rational. Meanwhile, the characteristics ofwriting style used by female Bataknese senior high school students in writing argumentativetextare emotional and sentimental, strong and logical. For Javanese students, thecharacteristics of writing style used by male are strong, logical, sentimental and terse, whilethe characteristics of writing style used by female are logical, terse, sentimental and silly. Thereason that caused different characteristic of their writing style are gender and culture.